INSTITUTIONS AND INDUSTRIAL DEVELOPMENT IN SABAH - Firdausi Suffian; Kasim Mansur; Ika Suzieana Jamluddin; Arnold Puyok; Azmi Abdul Majid (International Journal of Accounting, Finance and Business, 2022)
Industrialisation has been and continues to be lynchpin to modernise a state economy. Here, configuration of industrial policy is central in expanding and diversifying the downstream activities. Coherent industrial policy implementation depends upon the role of institutions that shape and facilitate elite policy makers in configuring and defining policy priority. It is important to note that institutions for every state differs significantly, this is due to the historical specificity, political events, norms that formed institutions. The institutional settings can condition policy actor defines interest and priority differently. In the case of Sabah, although the state is rich in resources, the implementation of industrial policy seems to be little success. The existing state’s economic structure does not support the expansion of downstream industry. The state continues to focus on resource extraction activities instead of moving up the value chain in the industrial sectors. This structural deficiency can be attributed to ineffective institutions which hinder coherent industrial policy implementation. Given the limited industrial development and policy-implementation gap, the state has fallen behind in many aspects of economic development.